2005
DOI: 10.1111/j.1600-0749.2005.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Early disease onset and increased risk of other autoimmune diseases in familial generalized vitiligo

Abstract: Generalized vitiligo is an autoimmune disorder in which acquired white patches of skin and overlying hair result from autoimmune loss of melanocytes from involved areas. Although usually sporadic, family clustering of vitiligo may occur, in a non-Mendelian pattern typical of multifactorial, polygenic inheritance. Sporadic vitiligo is associated with autoimmune thyroid disease, pernicious anemia, Addison's disease, and lupus; these same disorders occur at increased frequency in patients' first-degree relatives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
167
5
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(186 citation statements)
references
References 35 publications
6
167
5
8
Order By: Relevance
“…3 Other studies showed rates of 24.1% 13 21% , 12 and 17%. 21 However, data from previous studies show low prevalence, such as the values reported in a Chinese study that showed an association of 1.36% , 0.6% in Nigeria, 2.6% in Colombia and 3% in a Romanian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Other studies showed rates of 24.1% 13 21% , 12 and 17%. 21 However, data from previous studies show low prevalence, such as the values reported in a Chinese study that showed an association of 1.36% , 0.6% in Nigeria, 2.6% in Colombia and 3% in a Romanian population.…”
Section: Discussionmentioning
confidence: 99%
“…Increased frequency of type 1 diabetes mellitus and scleroderma was not found. 3,4,7,21 The presence of autoimmune hepatitis or parotiditis was not cited in the literature. The increased frequency of autoimmune diseases in patients with vitiligo suggests that all these conditions share a common etiologic factor.…”
Section: Discussionmentioning
confidence: 99%
“…27 Dave et al showed antibody positivity (anti-Tg, anti-TPO) in 31.4% of their cases in India against 10% of their controls. 15 In our study the anti TPO antibody positivity was more common in women in both the vitiligo and the control groups, though not statistically significant. A higher prevalence was also seen in other studies.…”
Section: Discussionmentioning
confidence: 71%
“…12,15 Autoimmune thyroid diseases often present with initial transient hyperthyroidism which may be missed and later progress to subclinical or overt hypothyroidism. Often, there is a delay in seeking medical advice and thyroid evaluation in our population which may explain the higher prevalence of hypothyroidism in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[2] First degree relatives have increased frequency of the same autoimmune diseases. [3] Its heritable constitutional predilection has found to be 20 to 30 %. 4 Polygenic multifactorial susceptibility that is triggered by environmental factors has been implicated in initiation of the disease.…”
Section: Introductionmentioning
confidence: 99%